2011
DOI: 10.1111/j.1365-2591.2011.01924.x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of calcium and silicon released from calcium silicate–based endodontic materials into root canal dentine

Abstract: Both Biodentine and MTA caused the uptake of Ca and Si in the adjacent root canal dentine in the presence of PBS. The dentine element uptake was more prominent for Biodentine than MTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
286
1
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(312 citation statements)
references
References 37 publications
12
286
1
13
Order By: Relevance
“…[13,25] It has been speculated that facilitating the formation of an interfacial layer between MTA and dentin would result in a favourable sealing ability since it would enhance the adhesion and the DR of MTA. [14,22,25] In the present study, adhesion of cement to CH-treated dentin was greater than the adhesion of cement to TAP-treated dentin. Shokouhinejad et al [21] suggested the application of non-setting CH to neutralize the pH and to increase the DR of MTA prior to the placement of MTA in a low-pH environment.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…[13,25] It has been speculated that facilitating the formation of an interfacial layer between MTA and dentin would result in a favourable sealing ability since it would enhance the adhesion and the DR of MTA. [14,22,25] In the present study, adhesion of cement to CH-treated dentin was greater than the adhesion of cement to TAP-treated dentin. Shokouhinejad et al [21] suggested the application of non-setting CH to neutralize the pH and to increase the DR of MTA prior to the placement of MTA in a low-pH environment.…”
Section: Resultsmentioning
confidence: 69%
“…[15,17,18] Both materials were reported to form an interfacial layer and a tag-like mineral structure extending to the dentinal tubules. [13,14,16,25] However, some differences in interfacial layers formed by MTA and BD were reported. [14,16] Han and Okiji [14] reported that BD released more Ca CC ions and formed more calcium phosphate precipitates and thicker Ca-and Si-rich dentin areas than MTA.…”
Section: Resultsmentioning
confidence: 99%
“…3 Biodentine was described as a bioactive dentin substitute with apatite formation after immersion in phosphate solution, 4 as the elemental uptake of Ca and Si into root canal dentin was found to be more prominent for Biodentine than for MTA. 5 Even though tricalcium silicate appears to be a common component of both MTA and Biodentine, X-ray diffractometry of unhydrated cements revealed that Biodentine consists of a triclinic form of tricalcium silicate, while MTA consists of the monoclinic form. 6 In comparison to other similar cements, Biodentine contains 30%-50% alumina (while Portland has less than 5%), 7 which produces an acid-resistant feature that may be useful in infection-laden sites of the human body, where the pH value drops significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Ca 3 SiO 5 is considered to be a good substitute for dentin in restorations 2,4 and is more resilient to shear force than other cements 10 . In another study, this material was shown to induce an inflammatory response upon initial contact with tissue, but later demonstrated biocompatible acceptance after 2 weeks 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The product consists of a powder (tricalcium silicate, calcium carbonate and zirconium oxide as a radiopacifier) and a liquid (containing calcium chloride and a water-soluble polymer) that are mixed together to form the cement 3,4 .…”
Section: Introductionmentioning
confidence: 99%